KOTAK KOSONG SEBAGAI PEMENANG: PERSPEKTIF SIYASAH DUSTURIYAH DALAM PEMILIHAN KEPALA DAERAH DI INDONESIA - yahwala Harahap, Muhammad Fadly; Rangkuti, Rahmad Efendi (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
The single candidate phenomenon often arises as a result of various factors, including the political system, election regulations, and the dominance of certain political forces. This raises concerns about the sustainability of a healthy democracy, because it reduces alternative choices for society. The research is normative research that uses a legislative and conceptual approach to review positive Indonesian law as well as the principles of Islamic law. Data was analyzed by data reduction, data presentation and drawing conclusions. The research results show that this phenomenon demands reformulation of election regulations to strengthen the quality of democracy and provide protection for people's political rights. In siyasah dusturiyah a single candidate can be considered to violate the spirit of shura because it reduces the community's right to choose from various alternative leaders. The principle of deliberation is the basis for leadership legitimacy. An empty box victory can be understood as a form of collective deliberation that rejects (public protest) the legitimacy of a single candidate. This shows that the public has not found a candidate who is considered worthy of leading. In the context of modern democracy, the empty box can be seen as a mechanism for channeling public dissatisfaction towards a single candidate. This is in line with the principle of amar ma'ruf nahi munkar which teaches people to reject injustice in the government system. From a siyasah dusturiyah perspective, efforts are needed to ensure leadership that is fair, transparent, and in accordance with the principles of shura (deliberation) in order to realize social justice in Indonesia's democratic system.